2010
DOI: 10.1358/mf.2010.32.10.1522224
|View full text |Cite
|
Sign up to set email alerts
|

Valeriana jatamansi partially reverses liver cirrhosis and tissue hyperproliferative response in rat

Abstract: Valeriana jatamansi (family, Valerianaceae) is a traditional medicinal herb in the Indian subcontinent. This study provides experimental evidence indicating the therapeutic effect of the extract prepared from the dried rhizome of the herb in an animal model of liver cirrhosis and on cell proliferation. Liver cirrhosis was induced in rats by thioacetamide (0.03% in drinking water for 16 weeks). After inducing liver cirrhosis, rats were administered the extract orally for 9 weeks. Treatment was found to partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Hence, we have enough time to make treatment on cirrhotic rats. In the literature, withdrawal of thioacetamide prior to the study was also acceptable as in Prasad study on cirrhotic rats (Prasad et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we have enough time to make treatment on cirrhotic rats. In the literature, withdrawal of thioacetamide prior to the study was also acceptable as in Prasad study on cirrhotic rats (Prasad et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is the end stage of liver fibrosis, which ultimately caused shrinkage of the liver, portal hypertension, and liver failure (Torok, ; Le Bousse‐Kerdiles, Martyre, & Samson, ). Prasad et al () provide evidences indicating the effect of the dried rhizome extract of V. jatamansi in an animal model of liver cirrhosis and on cell proliferation. Oral administration of extracts of this herb in the thioacetamide induced liver cirrhosis partially reverse the elevated levels of alkaline phosphatase, γ‐glutamyl transferase, and other biochemical markers of hepatic injury as well as the drug‐metabolizing enzymes.…”
Section: Medicinal Uses and Pharmacology Propertiesmentioning
confidence: 99%
“…Hypericum also has reports of liver damage in rat fetuses whose mothers were exposed to hypericin 11 . Despite reports of hepatic disorders related to the use of hypericum, kava and valerian in therapeutic doses of 900 mg/Kg, 300 mg/Kg and 150 mg/Kg respectively [29][30] , the obtained results showed that the use of combined smaller doses (1/3 of the therapeutic doses) are not detrimental considering the biochemical parameters.…”
Section: Discussionmentioning
confidence: 61%
“…Liver damage may be hepatocellular, causing increased serum of the alanine aminotransferase (ALT) and aspartate aminotransferase (AST) enzymes, or cholestatic, leading to increased bilirubin, alkaline phosphatase (ALP) and gamma-GT 29 . Studies have shown that chronic use of valerian causes hepatic toxicity in addition to side effects such as dyspepsia, allergic skin reactions, headache, and agitation 30 . Kava may exacerbate the status of patients with liver failure and hepatitis in those with a history of recurrent liver disease.…”
Section: Discussionmentioning
confidence: 99%